Pengaruh permainan lompat kelinci terhadap perkembangan motorik kasar di PAUD Rajo Sulah Kabupaten Kerinci - Eyzela Puputri; Indra Yeni (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2019)
This research originated from the fact that in Rajo Sulah PAUD Kerinci Regency tahat yaung childrens gross motor skills deloped optimally, children were unable to bend both legs and when jumping into a childs activity were still not balanced. Lack of gross motoric devalopment activities of children in the learning process. School in developing development. Therefore this rabbit jumping game is thought to have an influence on the childs motoric development. This study has an influence on the gross motor development of children. This study aims to determine the effect of rabbit jumping games on the gross motoric development of children in Rajo Sulah ECD Kerinci Regency. This type of researth is quantitative wiyh quasy experimental research menthods in the form of quasy experiments. Using the rabbit jumpng game affects the gross motoric development of children in Rajo Sulah ECD Kerinci Regency. Based on analysis, the average test results of the experimental proup were 84,89 and elementary school was 74,598 while in the control group there were 77,08 and elementary school at 67.274 in testing the hypothesis obtained tcount of 2.1764498 and ttable of 2.074 at the real leve α =0,05 and dk=22, it can be concluded that the rabbit jumping game proved to have a large influence on the gross motoric development of children in Rajo Sulah PAUD Kerinci Regency.